Being honest won't pay. Seven- but not 5-year-olds begin to predict that others will lie for reputational reasons. - Mareike Klafka; Ulf Liszkowski (PLoS ONE)
Children begin to manage their reputation around school-age, but it remains unclear when they start to explicitly reason about reputational strategies such as lying from a third-person perspective. The current study investigated whether 5- and 7-year-old children would explicitly predict reputational lying in the context of a third party interaction. Participants were told hypothetical stories and asked to predict whether a protagonist would lie to a peer character about a selfish resource allocation. Results revealed that about half of the 7-year-olds and neglectable few of the 5-year-olds began to predict that the protagonist would lie to his peer out of reputational concern and whitewash the selfishly distributed amount. The prediction of reputational lying did not differ for ingroup or outgroup third parties. Seven-year-olds justified their prediction of a lie with reference to how the protagonist would look to others. While reputational lying has been shown in 5-year-olds in comparable interactive scenarios with peers, a more abstract, explicit understanding of reputational lying seems to be a more complex cognitive ability, emerging around the age of 7 years.